Apoptotic Effect of Bleomycin Formulated in Cinnamon Oil Nanoemulsion on HeLa Cervical Cancer Cells - Alkhatib, Mayson H. (Asian Journal of Pharmaceutics (AJP), 2020)
Background: Using the essential oils with the cytotoxic agents in nanocarrier may have a potent effect on the cancer cells. Materials & Methods: A nanoemulsion (NE) consisting of the cinnamon oil (free NE) and bleomycin-loaded NE (BLEO-NE) was formulated, physically characterized by the zetasizer, and evaluated in vitro to determine its antineoplastic activity against HeLa cervical cancer cells. The cell viability, morphological changes, apoptosis, and DNA fragmentation of the cancer cells, subjected to the free NE and BLEO-NE, were examined by the cell counting kit-8 assay, light microscopy, annexin V-fluorescein isothiocyanate, and ELISA cell death detection, respectively. Results: It has been found that the dispersed nanodroplets of free NE had mean particle diameter and zeta potential of 119.60 ± 1.20 nm and −0.913± 0.001 mV, respectively, but they had got enlarged to 524.33 ± 1.10 nm and 0.537 ± 0.002 mV, respectively, when BLEO was loaded (BLEO-NE). The results of the cell viability, apoptosis, and cell death detection have demonstrated that BLEO-NE had a higher apoptotic effect than free BLEO. Conclusion: These findings suggest that the combination therapy of BLEO with NE-based cinnamon oil has a potential anticancer activity